Extended cleavage specificity of sheep mast cell protease-2: A classical chymase with preference to aromatic P1 substrate residues. (March 2019) - Fu, Zhirong; Akula, Srinivas; Thorpe, Michael; Chahal, Gurdeep; de Garavilla, Lawrence; Kervinen, Jukka; Hellman, Lars
Abstract: Serine proteases constitute the major protein content of mammalian mast cell granules and the selectivity for substrates by these proteases is of major importance for the role of mast cells in immunity. In order to address this subject, we present here the extended cleavage specificity of sheep mast cell protease-2 (MCP2), a chymotrypsin-type serine protease. Comparison of the extended specificity results to a panel of mammalian mast cell chymases show, in almost all aspects, the same cleavage characteristics. This includes preference for aromatic residues (Phe, Tyr, Trp) in the P1 position of substrates and a preference for aliphatic residues in most other substrate positions around the cleavage site. MCP2 also cleaved, albeit relatively low efficiency, after Leu in the P1 position. In contrast to the human, mouse, hamster and opossum chymases that show a relatively strong preference for negatively charged amino acids in the P2′position, the sheep MCP2, however, lacked that preference. Therefore, together with the rat chymase (rMCP1), sheep MCP2 can be grouped to a small subfamily of mammalian chymases that show fairly unspecific preference in the P2′position. In summary, the results here support the view of a strong evolutionary conservation of a potent chymotrypsin-type protease as a key feature of mammalian mast cells. Highlights: A chymotryptic enzyme is a key characteristic of mammalian mast cells. The sheep MCP2 belongs to a small subfamily of chymases without preference for negative amino acids in the P2′position. Serine proteases are the most abundant granule constituents of mammalian mast cells. A number of potential physiological functions have been identified for these mast cell proteases.